Government shareholders, wasted resources and climate ambitions: why is China still building new coal-fired power plants?. (2nd January 2023) - Clark, Alex; Benoit, Philippe; Walters, Jonathan
ABSTRACT: Despite its carbon neutrality commitments and the prospect of increasingly stringent climate policy measures, China is continuing to build new coal-fired power plants. In assessing the expected performance of these investments, it is helpful to analyse them through an 'economic' framework measuring a broader view of the country-level economic returns on new coal power investments, as a complement to the plant-level financial analysis framework commonly used to assess stranded asset risks. This simplified economic framework, in which inputs and outputs are measured according to the costs and benefits they generate for the national economy, leads to markedly different dynamics than financial analysis alone. This framework can help China to avoid 'wasting' scarce public resources by over-investing in new uneconomic power plants through its state-owned enterprises. Applying this approach to a representative new coal plant in China shows that modest shadow carbon pricing (rising from US$15/tCO2 in 2026, to US$30/tCO2 in 2041) eliminates the expected value of the project to China's economy. Caps on coal-fired electricity generation have less impact on economic returns, but severely undermine financial returns, potentially making such caps a more effective short-term policy tool to dissuade company executives from making new coal investments. Without carbon pricing, only a moratorium on coal-fired power generation in 2030 or earlier prevents new plants from realizing a positive economic return. Comparing these results with an alternative solar/storage investment suggests the renewable option generates higher economic returns than the coal plant under modest shadow carbon pricing and lower electricity storage costs. Key policy insights Economic analysis of proposed coal plants complements plant-level financial analysis and better captures governments' interests in these projects. Both economic and financial analyses are relevant to the decision-making of government shareholders. State-led coal plant investments in China today is likely to be economically wasteful under modest future climate policy scenarios, particularly in light of declining levelized costs of renewable alternatives. This framework for combined financial and economic analysis also applies to other countries' proposed investments in carbon-intensive power generation. The framework is particularly pertinent for countries with state-led coal power investments planned, including India, Indonesia, Pakistan, South Africa, and Vietnam.